Experiencing materiality : museum perspectives - Gamberi, Valentina (Berghahn Books, 2021)
"Representing a cutting-edge study of the junction between theoretical anthropology, material culture studies, religious studies and museum anthropology, this study examines the interaction between the human and the nonhuman in a museum setting usually defined as 'non-Western', 'non-scientific' and 'religious.' Combining an on-site analysis of exhibitive spaces with archival research and interviews with museum curators, the chapters highlight contradictions of museum practices, and suggests that museum practitioners use museum spaces and artefacts as a way of formulating new theoretical stances in material culture studies, thus viewing museums as producers of theories together with affective engagements"--